2008
DOI: 10.1055/s-2007-964970
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intensified Military Field Training on Jumping Performance

Abstract: A sensitive, reliable, field-expedient test may be valuable for monitoring interventions during periods of anticipated physical performance decline. The purpose of this study was to determine the capabilities of unloaded jumping tests for detecting decrements in physical performance following eight days of military sustained operations. Twenty-nine U. S. Marines (24 +/- 1 y; 180 +/- 6 cm; 82.5 +/- 8.2 kg) performed 1, 5 and 30 repetition(s) of unloaded countermovement jumps (UJ) before and after eight days of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
50
2
10

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 18 publications
10
50
2
10
Order By: Relevance
“…Furthermore, we observed reduced maximal power in the counter movement and squat jumps in the post-intervention testing. After periods of strenuous exercise training, reduced power during maximal muscle contraction has been shown to be a good indicator of muscular fatigue (Andersson et al 2008;Welsh et al 2008). Considering our observations 7 days post-intervention, it could be concluded that muscular fatigue limited the achievement of HR max and the degree of improvement in PPO.…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, we observed reduced maximal power in the counter movement and squat jumps in the post-intervention testing. After periods of strenuous exercise training, reduced power during maximal muscle contraction has been shown to be a good indicator of muscular fatigue (Andersson et al 2008;Welsh et al 2008). Considering our observations 7 days post-intervention, it could be concluded that muscular fatigue limited the achievement of HR max and the degree of improvement in PPO.…”
Section: Discussionmentioning
confidence: 67%
“…The traditional use of 95% confidence intervals applied to a 3.5% CV evidentiary standard can even be viewed as conservative (Hopkins 2004;Hopkins et al 1999), thus strengthening our interpretation of importance. By virtue of comparison, it requires 8 days of chronic activity, sleep deprivation, and underfeeding to achieve the same *4% decrement in jump performance (Welsh et al 2008) achieved herein with a -3.2 ± 0.5 kg (-3.8 ± 0.6%) total body water deficit.…”
Section: Discussionmentioning
confidence: 73%
“…Gradual losses of body mass (over days or longer) achieved with energy and fluid restrictions usually result in losses of lean tissue mass, fat mass, and water mass (Nindl et al 2002;Welsh et al 2008). Gradual mass losses appear to reduce strength and power of the leg extensor muscles (Nindl et al 2002;Welsh et al 2008) but produce no effect (Fogelholm et al 1993), or substantially impair (Chicharro et al 1998;Welsh et al 2008) vertical jump performance. This reflects that the trade-off between lost strength and lost mass yields no gain in S/M and provides no jumping advantage; it may even have a detrimental effect.…”
Section: Introductionmentioning
confidence: 99%
“…A 2-min push-up test has previously been used as a component in a model to predict battlefield performance (Harman et al 2008). The capacity to develop lower limb power was assessed using an unloaded vertical squat jump, which has been reported to correlate well with simulated battlefield performance (Harman et al 2008;Welsh et al 2008) and be sensitive to the effect of intensified military training (Nindl et al 2002(Nindl et al , 2007. Isometric handgrip strength has been previously used to monitor performance changes in military subjects (Legg and Patton 1987;Patton et al 1989) and was measured to assess if fatigue occurred from continuously gripping a seat rail to maintain postural stability during the transit.…”
Section: Physical Performance Testsmentioning
confidence: 99%